Antifungal activity of in vitro aqueous and alcoholic extracts of Barije root (Ferula gummosa) - Mohammad Salehi; Masoud Hashemi Karoi; Ayatollah Nasrollahi omran; Masoud Mobini; Maryam Asghar Hedari (مجله دانشگاه علوم پزشکی بیرجند, 2015)
Background and Aim: Ferula gummosa Boiss. (Barije) is an Iranian indigenous plant that has medical and antifungal properties. The current study was done to determine the effect of aqueous an alcoholic extracts of Ferula gummosa Boiss root on in vitro growth of fungi. Materials and Methods: In this experimental study, the plant was dried in the dark and aqueous, alcoholic extracts of its root powder were prepared using Soxhlet method. Then, the efficacy of 0.1 dilutions of different quantities of the extracts on strains of Candida albicans (PTCC 5027), Trichophyton rubrum (PTCC5143), and Aspergillus fumigatus (PTCC 5009) were evaluated employing Disk diffusion, Agar-well diffusion, Minimum Inhibitory Concentration (MIC), and Minimum Fungicidal Concentration (MFC) methods. Results: No inhibited effect was observed in Disk diffusion and Agar-well diffusion methods. MIC and MFC values of all extracts for Aspergillus fumigatus and Trichophyton rubrum were more than 5×104mg/ml. The MIC values of ethanol and methanol extract for Candida albicans were 3.12×103 and 1.25×104mg/ml, respectively but the MFC values were 1.25×104 and 2.5×104mg/ml, respectively. Conclusion: Methanol and ethanol extracts proved to have antifungal activity against Candida albicans yeast in vitro while the fungi of Aspergillus fumigatus and Trichophyton rubrum had no sensitivity to these types of extracts.